Peeping Techno-Toms and the Fourth Amendment: Seeing through Kyllo's Rules Governing Technological Surveillance - Slobogin, Christopher (2002)
This article suggests that the Supreme Court's decision in Kyllo v. United States may not be as protective of the home as it first appears. Kyllo held that use of a thermal imager to detect heat sources inside the home is a fourth amendment search, requiring a warrant and probable cause. But it also held that use of technology that is in general public use or that only discovers what a naked eye observer could see from a public vantage point is not a search, even when the location viewed is the interior of the home. This article shows that both the general public use and naked eye exceptions are inscrutable, conceptually incoherent, and normatively objectionable. In making the normative argument in favor of eliminating both exceptions, it looks at historical material, current Peeping Tom legislation and empirical findings. It then argues that technological surveillance of the home should be regulated either through a proportionality approach, which varies the level of cause the government must have to search with the search's intrusiveness, or through a legislative approach, using Title III's regulation of communications surveillance as the model